Evaluation of iron, zinc, potassium and proximate qualities of five Musa genotypes - Baiyeri, K.; Ede, A.E.; Otitoju, G.T.; Mbah, O.; Agbo, E.; Tenkouano, A.; Faturoti, B. (2009)
The study was conducted to determine iron, zinc and potassium contents and the proximate qualities of ripe and unripe fruits of five Musa genotypes (‘Agbagba’, ‘FHIA 21’, ‘PITA 14’, ‘PITA 24’ and ‘30456-2’). Methodology and results: The genotypes were grown under organic and inorganic fertilizer application systems. Three bunches per genotype were harvested from each system. Fruit samples were obtained from the second proximal hands of each bunch. Fruit metric traits (weight, circumference, length and edible proportion), proximate qualities, Fe, Zn and K were determined. Genotypes varied significantly (P < 0.05) in all the fruit metric traits and some proximate quality traits, notably ash and carbohydrate contents. Although the landrace (Agbagba) produced larger fruit size, the hybrids had significantly higher Zn and Fe contents. Genotypes ‘PITA 14’ and ‘30456’ had higher values for Zn and Fe, respectively. Proximate traits except percent ash and carbohydrate were statistically the same across the genotypes. Organic fertilizer use improved fruits metric traits but most proximate traits were similar in the organic and inorganic fertilizer systems. The concentrations of Fe, Zn and K were statistically similar in both fertilizer systems, although fruits harvested from inorganic fertilizer system tended to have higher values. Unripe fruits had higher energy value but the ash, Fe, fat, fibre and protein contents were higher in the ripe fruits. Conclusion and application of findings: The study revealed that producing plantains with organic fertilizer alone, does not in anyway result to fruits deficient in basic nutrients. Besides, higher values of Zn were obtained in the unripe than in the ripe fruits of ‘FHIA 21’and ‘30456-2’. In contrast, the values of Fe were higher in ripe fruits than unripe in most of the genotypes except ‘FHIA 21’. The preponderance of key micronutrients in the hybrids suggests that micronutrient deficiencies could be alleviated if these hybrids are sufficiently produced and included in our diets.